Comparative Analysis of Teaching Methods: A Cross-Cultural Study of Chinese and American Educational Systems - Lu, Yulong (Transactions on Social Science, Education and Humanities Research, 2024)
Chinese and American educational systems represent two separate paradigms that have been influenced by many historical, cultural, and sociological elements. This paper examines the complex interactions defining their instructional strategies, cultural influences, and curriculum priorities. The study analyzes disparities, clarifies how cultural differences affect learning, and offers practical suggestions for international learning environments. It contrasts the participatory, inquiry-based paradigm used in the U.S. with China's teacher-centered approach and rote memorization. The emphasis on knowledge acquisition in Chinese curricula contrasts with that on application and critical thinking in American curricula. The results show the complex effects of these instructional strategies, with Chinese students performing well on standardized tests but having trouble with critical thinking, whereas American students have great analytical skills but struggle with test performance. The psychological and emotional health of the pupils is affected, with American students benefiting from a climate that supports self-expression while Chinese kids are subjected to intense pressure. The duties of teachers vary greatly, with American colleagues encouraging student engagement and critical thought while Chinese educators frequently serve as knowledge transmitters. This study emphasizes that there is no single model for effective teaching and offers suggestions for improving classroom instruction in China, including enhancing teaching resources, encouraging individualized learning, funding teachers' ongoing professional development, and involving parents in the educational process.